Tuning the Photocatalytic Performance of Ruthenium(II) Polypyridine Complexes Via Ligand Modification for Visible‐Light‐Induced Phosphorylation of Tertiary Aliphatic Amines. Issue 1 (14th November 2022) - Mahmood, Zafar; He, Jia; Cai, Shuqing; Yuan, Zhanxiang; Liang, Hui; Chen, Qian; Huo, Yanping; König, Burkhard; Ji, Shaomin
Abstract: Tuning the redox potential of commonly available photocatalyst to improve the catalytic performance or expand its scope for challenging synthetic conversions is an ongoing demand in synthetic chemistry. Herein, the excited state properties and redox potential of commercially available [Ru(bpy)3 ] 2+ photocatalyst were tuned by modifying the structure of the bipyridine ligands with electron‐donating/withdrawing units. The visible‐light‐mediated photoredox phosphorylation of tertiary aliphatic amines was demonstrated under mild conditions. A series of cross‐dehydrogenative coupling reactions were performed employing the Ru II complexes as photocatalyst giving the corresponding α‐aminophosphinoxides and α‐aminophosphonates via carbon‐phosphorus (C−P) bond formation. Abstract : The redox potential of ruthenium(II) complexes were tuned with the aim to expand their applicability as photocatalyst for synthetic conversion. This resulted in an extended scope of the photoredox phosphorylation of tertiary aliphatic amines using a new ruthenium complex as photocatalyst.